The Vietnam War: international, criminal law, and sociological aspects - Lopicic Jancic, Jelena; Vasic, Ljubica (Sociološki pregled, 2025)
The paper analyzes the Vietnam War from the perspective of international law, criminal law, and sociology, as well as its broader impact on society in general. Historically, most wars have been accompanied by violations of international and criminal law, especially regarding the treatment of civilian population, prisoners of war, the wounded, and the sick. The Vietnam War stands as one of the most drastic examples of systematic violence and war crimes in the modern era, with many crimes remaining without an adequate judicial response, while the topic itself has been marginalized in jurisprudence. This paper aims to critically examine the legal framework applicable to the Vietnam War, as well as the practice of (non-)sanctioning war crimes committed during that war.